1999
DOI: 10.1021/cm9900756
|View full text |Cite
|
Sign up to set email alerts
|

Alumination and Ion Exchange of Mesoporous SBA-15 Molecular Sieves

Abstract: Mesoporous silica SBA-15 molecular sieve has been synthesized and incorporated with aluminum via three different postsynthesis procedures by reacting SBA-15 with AlCl 3 in dry ethanol (route 1), with aluminum isopropoxide in dry hexane (route 2) and with an aqueous solution of sodium aluminate (route 3) followed by calcination. Characterization by transmission electron microscopy, N 2 adsorption, electron probe microanalysis, powder X-ray diffraction, 27 Al magic-angle-spinning NMR, and electron spin resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
266
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(281 citation statements)
references
References 22 publications
14
266
0
1
Order By: Relevance
“…Different mesoporousm aterials, silica MCM-41, [31] MCM-48, [31] and SBA-15, [32] aluminosilica AlSBA-15, [33] Information). When the sulfonated phosphine (MeO-TPPMS, 1b)i su sed, the immobilization can take place through hydrogen bonding between the silanol groups on the silica support and the sulfonate group in the ligand (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different mesoporousm aterials, silica MCM-41, [31] MCM-48, [31] and SBA-15, [32] aluminosilica AlSBA-15, [33] Information). When the sulfonated phosphine (MeO-TPPMS, 1b)i su sed, the immobilization can take place through hydrogen bonding between the silanol groups on the silica support and the sulfonate group in the ligand (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…[33] Am ixture of silica SBA-15 (2.0 g, approx. 32 mmol) and AlCl 3 (0.134 g, 1.10 mmol) was heated to reflux in anhydrous ethanol at 80 8Cf or 10 h. The resulting solid was filtered, washed repeatedly with anhydrous ethanol, and dried in air at room temperature.…”
Section: Syntheses Of Alsba-15mentioning
confidence: 99%
“…The short column SBA-15 type supports used in this work were prepared by dissolving 4 g of Pluronic P123 (EO 20 PO 70 EO 20 ) in 160 g of 2 M HCl solution at 35 • C, followed by adding 9.1 ml of tetraethyl orthosilicate (TEOS), 0.66 g of ZrOCl 2 and different amounts of Al 2 (SO 4 ) 3 . The mixture was stirred at 35 • C for 20 h, and then aged at 85 • C for 48 h. After the procedures described above, the pH of the mixture was adjusted to 7.5 by adding NH 4 OH dropwise at room temperature and the obtained mixture was hydrothermally heated again at 85 • C for 48 h. The recovered soil was extensively washed with deionized water and dried at 60 • C for 24 h. Template removal was performed by calcinations in air using two successive procedures, i.e., heating at 350 • C for 3 h and then at 550 • C for 4 h, to prevent the silica matrix from shrinking, and hence maintained the original size and volume of micro-and mesopores.…”
Section: Support Preparationmentioning
confidence: 99%
“…The procedure of direct-synthesis is relatively simple, however, only a small amount of heteroatoms can be introduced into the mesoporous silica. Compared with directsynthesis, post-grafting can introduce more heteroatoms into the framework of mesoporous silica, however, the post-grafting routes are very complicated and the uniform mesostructure of products are sometimes severely destroyed [20]. Recently, Wu et al [21] reported a simple and efficient "pH-adjusting" approach which can introduce large amount of heteroatoms into mesoporous silica without destroying its original mesostructure.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prove that the reaction was heterogeneously catalyzed, and to exclude the possibility of homogeneous catalysis, filtration test was carried out [9]. After addition of the substrate to the supernatant of the fifth cycle, the hydrogenation was continued for 2 h. No further reaction was observed, whereas the original catalyst in the sixth cycle completely hydrogenated the substrate.…”
Section: Immobilization and Characterization Of The Catalystmentioning
confidence: 99%